Fe-Co bimetallic active site catalyst as well as preparation method and application thereof

By constructing the Fe-Co bimetallic active catalyst and adjusting its high-active interface, the problem of high C5+ selectivity in the synthesis of low-carbon olefins by existing iron-based catalysts is solved, and efficient low-carbon olefin selectivity and product distribution concentration are achieved.

CN119608170APending Publication Date: 2025-03-14SHANDONG ENERGY GROUP COAL GASIFICATION & NEW MATERIALS TECHNOLOGY CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411780668.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing iron-based catalysts have high C5+ selectivity in the synthesis of low-carbon olefins by CO2, resulting in inconcentrated product distribution and insufficient selectivity of low-carbon olefins.

Method used

The Fe-Co bimetallic active catalyst was constructed by the sol-gel method, and the Fe5C2-FeCo high-active interface was adjusted through a coordinated regulation strategy, reducing the selectivity of C5+ and improving the selectivity of low-carbon olefins.

Benefits of technology

High CO2 conversion rate, low CO selectivity and excellent low carbon olefin selectivity are achieved, and the product distribution is more concentrated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005172703570000151
    Figure BDA0005172703570000151
  • Figure BDA0005172703570000161
    Figure BDA0005172703570000161
  • Figure HDA0005172703580000011
    Figure HDA0005172703580000011
Patent Text Reader

Abstract

The invention provides a preparation method of a Fe-Co bimetallic active site catalyst, which comprises the following steps: mixing ferric salt, cobalt salt and citric acid, heating, stirring and dissolving, and heating to obtain a gel-state compound; continuously heating the gel-state compound, and calcining to obtain a Fe-Co solid catalyst; and dropwise adding the sodium salt solution into the Fe-Co solid catalyst, and carrying out ultrasonic treatment, drying and grinding to obtain the Fe-Co bimetallic active site catalyst. The Fe-Co bimetallic active site catalyst with a high-activity interface is constructed, and the catalyst shows excellent performance in the aspect of directional and high-yield synthesis of low-carbon olefin through carbon dioxide hydrogenation. The Fe-Co bimetallic active catalyst is prepared by adopting a sol-gel method, Fe-Co bimetallic active sites are synergistically adjusted, a Fe5C2-FeCo high-activity interface is constructed, and the Fe-Co bimetallic active catalyst shows excellent CO2 conversion rate, relatively low CO selectivity and excellent low-carbon olefin selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of olefin synthesis, and in particular to an Fe-Co bimetallic active site catalyst and a preparation method and application thereof. Background Art

[0002] Carbon dioxide is an important greenhouse gas, and the development of effective CO2 conversion and utilization technology is an important way to achieve the "dual carbon" goal. CO2 is effectively captured and further converted into high-value-added chemicals through thermal catalysis. This process can effectively reduce the concentration of CO2, greatly promoting the circular carbon economy and net zero emissions. Low-carbon olefins are important raw materials in the chemical industry, mainly derived from the refining of traditional fossil resources such as petroleum. Therefore, the development of CO2 hydrogenation technology to replace traditional fossil energy to produce low-carbon olefins is a major demand in my country's energy, environment and ecology fields, and has attracted the attention of more and more researchers.

[0003] At present, the pathways for synthesizing light olefins by thermal catalytic carbon dioxide hydrogenation mainly focus on methanol to olefins (MTO) and improved Fischer-Tropsch olefins (FTO).

[0004] Iron-based catalysts are widely used in heterogeneous catalytic CO2-FTS of light olefins due to their catalytic activity in reverse water gas shift (RWGS) and Fischer-Tropsch synthesis (FTS) reactions, but the process has problems such as low activity and poor selectivity. Derivatization of iron-based catalysts used for CO2 hydrogenation can obtain two types of active phases for improved reactions, including Fe3O4 phases for CO2 reduction to CO reaction (i.e., RWGS) and Fe5C2 phases for CO hydrogenation to high value-added chemicals. Alkali metals are widely used as chemical promoters (Na, K, etc.) in the preparation of high value-added chemicals from CO2 via FTS. Alkali metals can change the electron density of FTS catalysts and act as electron donors, thereby further effectively promoting the adsorption and activation of CO2 and accelerating the formation of carbides on iron-based catalysts. On the other hand, the introduction of alkali metals can adjust the hydrogen-carbon ratio adsorbed on the catalyst surface, reduce the activation energy of the reaction process, and further promote the formation and desorption of olefins on the catalyst surface.

[0005] Li Wei et al. successfully constructed a mesoporous carbon-enclosed FeO-Fe3C active site catalyst by introducing non-metallic elements (B, P, F and Se). The catalyst showed excellent activity and stability at 320℃, 3.0MPa, H2 / CO2=3.0, and GHSV=12000mL / g cat / h, with a carbon dioxide conversion rate of 42.6%, a carbon monoxide selectivity of 23.45%, and a light olefin selectivity of 53.4% ​​(Chemical Engineering Journal, 2023, 477, 147153). Xin Zhong et al. successfully constructed a new hybrid catalyst Fe2O3@ZrO2 through the pyrolysis strategy of a bimetallic organic framework (NH2-MIL-88B@UiO-66), which showed a significant light olefin space-time yield (12.7mmol g) at 340℃, 3.0MPa, CO2 / H2=1:3, 10000mL / g cat / h. -1 h -1 )(Chemical Engineering Journal, 2024, 484, 152926).

[0006] At present, some catalysts used in the field of CO2 hydrogenation to prepare light olefins have applied for relevant patents. Take the following reported patent as an example for detailed description: CN112174764A is publicly named: Application of iron-based catalysts in catalytic carbon dioxide hydrogenation to synthesize light olefins. An alkali metal-assisted iron-based catalyst was reported, which showed a CO2 conversion rate of more than 42% and a light olefin selectivity of 44.6%.

[0007] Although alkali metal-impregnated iron-based catalysts show good performance in CO2 hydrogenation to synthesize light olefins, iron-based catalysts still show strong chain growth ability in CO2 hydrogenation catalysis, which will lead to unconcentrated product distribution and C5+ selectivity still accounts for a large proportion.

[0008] Therefore, reducing the selectivity of C5+ and increasing the selectivity of low-carbon olefins are technical problems that need to be solved urgently. Summary of the invention

[0009] In view of this, the technical problem to be solved by the present invention is to provide a Fe-Co bimetallic active site catalyst with excellent performance. The catalyst of the present invention has a high CO2 conversion rate, a low CO selectivity, and excellent low-carbon olefin selectivity.

[0010] The inventors found that if higher selectivity for light olefins is to be obtained, it is necessary to introduce other components to further regulate the distribution of products and further improve the selectivity of light olefins. Synergistically regulating the bimetallic layout and constructing a catalyst with a highly active interface is expected to regulate the product distribution of CO2 hydrogenation and reduce the selectivity of C5+. The inventors used a sol-gel method to construct a series of Fe-Co bimetallic active catalysts through a synergistic regulation strategy, regulating the Fe5C2-FeCo high-activity interface, and improving the selectivity of light olefins.

[0011] The present invention provides a method for preparing a Fe-Co bimetallic active site catalyst, comprising the following steps:

[0012] A) mixing iron salt, cobalt salt and citric acid, heating and stirring to dissolve, and heating to obtain a gel composite;

[0013] B) continuing to heat the gel composite and then calcining it to obtain a Fe-Co solid catalyst;

[0014] C) dropping the sodium salt solution into the Fe-Co solid catalyst, ultrasonicating, drying and grinding to obtain the Fe-Co bimetallic active site catalyst.

[0015] The preparation method of the Fe-Co bimetallic active site catalyst provided by the invention comprises mixing iron salt, cobalt salt and citric acid, and heating and stirring to dissolve.

[0016] Firstly, the iron salt and the cobalt salt are dissolved in deionized water, and citric acid is added after heating, and the mixture is stirred continuously and heated further until a gel-like complex is formed.

[0017] The heating temperature is 20-60°C for 1-3 hours, and then the stirring is continued at 20-60°C for 1-3 hours, and then the temperature is continued to be raised to 70-120°C. The temperature for continued heating can be 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, or a range between any two of the above.

[0018] The iron salt is nitrate, acetate or chloride of iron; it can be ferric nitrate, ferric acetate or ferric chloride;

[0019] The cobalt salt is a nitrate, acetate or chloride of cobalt; it may be cobalt nitrate, cobalt acetate or cobalt chloride.

[0020] The molar ratio of iron to cobalt in the Fe-Co bimetallic active site catalyst of the present invention is 0.5-2, specifically 0.5:1, 1:1, 1.5:1 or 2:1, or a range between any two of the above, and 1:1 is particularly preferred.

[0021] The catalyst is derived from spinel material as a precursor to obtain Fe-Co bimetallic active sites with Fe5C2-FeCo high-activity interfaces in different proportions.

[0022] The citric acid described in the present invention is hydrous citric acid or anhydrous citric acid; the molar ratio of the added amount of the citric acid to the metal content is 4:3.

[0023] The gel composite is further heated and calcined to obtain a Fe-Co solid catalyst.

[0024] The gel-state composite is continuously heated to form a magma-like substance; the magma-like substance is transferred to a muffle furnace and heated to 300-700° C. at a heating rate of 0.5-10° C. / min for calcination for 2-8 hours and then cooled to room temperature.

[0025] The calcination temperature is 300-700°C; specifically, it can be 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C or 700°C; or a range between any two of the above.

[0026] The calcination time is 2 to 8 hours; specifically, it can be 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours; or a range between any two of the above.

[0027] The obtained solid was ground and washed several times, and then placed in an oven at 60-100° C. for drying for 2-12 hours; the obtained sample was ground into powder.

[0028] The washing may be carried out with a mixture of deionized water and anhydrous ethanol, or with deionized water and anhydrous ethanol alternately.

[0029] The sodium salt solution is dripped into the Fe-Co solid catalyst. The dripping speed of the present invention is not limited and can be any speed known to those skilled in the art.

[0030] Preferably, the sodium salt is dissolved in deionized water to obtain a sodium salt solution; the sodium salt is sodium carbonate, sodium bicarbonate or sodium nitrate. The present invention adopts an equal volume impregnation method to load the Na salt.

[0031] After the soluble Na salt is dissolved, it is dropped into the Fe-Co catalyst and ultrasonicated until it is dry and ground to obtain the Fe-Co bimetallic active site catalyst.

[0032] The Fe-Co bimetallic active site catalyst of the present invention has a unique high-activity interface and contains alkali metal ions.

[0033] The theoretical molar content of Na is 0.01 to 0.04 of Fe, and specifically can be 0.01, 0.02, 0.03 or 0.04, or a range between any two of the above, and is particularly preferably 0.02.

[0034] The molar ratio of Fe:Co is in the range of 0.5-2. The molar ratio of the electron auxiliary agent Na is in the range of 0.01-0.04 with reference to Fe.

[0035] In the present invention, the drying is drying in an oven at 70-120° C. for 2-12 hours; the grinding is granulating into 10-60 meshes after grinding.

[0036] The present invention provides a Fe-Co bimetallic active site catalyst, which is prepared by the preparation method described in any one of the above technical solutions.

[0037] The molecular formula of the Fe-Co bimetallic active site catalyst provided by the present invention is Na a Fe b Co c Where a is 0.01 to 0.04; b is 1 or 2; c is 1 or 2.

[0038] The molecular formula of the Fe-Co bimetallic active site catalyst provided by the present invention can be Na 0.02 Fe2Co 1、 Na 0.02 Fe1Co 1、 Na 0.02 Fe1Co 2、 Na 0.01 Fe1Co 1、 Na 0.03 Fe1Co 1、 Na 0.04 Fe1Co1.

[0039] The catalyst prepared by the present invention has the characteristics of cheap and readily available raw materials, a simple preparation process, and strong operability and repeatability, which is beneficial for mass production of catalysts.

[0040] The Fe-Co bimetallic active site catalyst with a high active interface prepared by the present invention has stable properties and high CO2 hydrogenation catalytic activity.

[0041] The synergistic regulation layout strategy of the Fe-Co bimetallic active site catalyst prepared by the present invention constructs a highly active interface and exhibits high CO2 conversion rate, low CO selectivity, and excellent low-carbon olefin selectivity.

[0042] The present invention provides the use of the Fe-Co bimetallic active site catalyst prepared by any one of the preparation methods described above in the preparation of light olefins. The light olefins are olefins with 2 to 4 carbon atoms.

[0043] The present invention provides a method for synthesizing light olefins by hydrogenating CO2, comprising:

[0044] The Fe-Co bimetallic active site catalyst prepared by the preparation method described in any one of the above technical solutions is reduced and activated, and then subjected to hydrogenation reaction under the conditions of a mixed gas of H2 and Ar with CO2 as the reaction gas.

[0045] In some embodiments of the present invention, the reduction activation parameters include: using pure hydrogen (purity ≥ 99%) at normal pressure, heating to 200-800°C at a heating rate of 0.5-15°C / min and maintaining for 2-12h.

[0046] The heating temperature is 200-800°C; specifically, it can be 200°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 800°C; or a range between any two of the above.

[0047] The low-carbon olefin is an olefin having 2 to 4 carbon atoms.

[0048] In some embodiments of the present invention, the molar ratio of H2:CO2 in the mixed gas is 0.1 to 5.

[0049] In one embodiment of the present invention, the ratio of the raw gas is H2 / CO2 / Ar=68 / 27 / 5 (v / v / v)

[0050] The mixed gas flow rate range is 5 to 80 mL / min; specifically, it can be 5 mL / min, 10 mL / min, 20 mL / min, 30 mL / min, 40 mL / min, 50 mL / min, 60 mL / min, 70 mL / min, 80 mL / min; or a range value between any two of the above.

[0051] The hydrogenation reaction temperature is 180-550°C, preferably 300-360°C, specifically 180°C, 200°C, 300°C, 320°C, 340°C, 360°C, 400°C, 450°C, 500°C, 550°C, or any range between any two of the above.

[0052] The hydrogenation reaction pressure ranges from 0.1 to 6 MPa; specifically, it can be 0.1 MPa, 0.5 MPa, 1 MPa, 2 MPa, 3 MPa, 4 MPa, 5 MPa or 6 MPa; or a range between any two of the above.

[0053] The present invention provides a preparation method of a Fe-Co bimetallic active site catalyst, comprising the following steps: A) mixing iron salt, cobalt salt and citric acid, heating and stirring to dissolve, and heating to obtain a gel-state complex; B) continuing to heat the gel-state complex and calcining to obtain a Fe-Co solid catalyst; C) dripping a sodium salt solution into the Fe-Co solid catalyst, ultrasonicating, drying, and grinding to obtain a Fe-Co bimetallic active site catalyst. The present invention discloses a Fe-Co bimetallic active site catalyst having a high active interface constructed by a synergistic regulation layout strategy, and the catalyst exhibits excellent performance in the directional and high-yield synthesis of light olefins, and belongs to the field of CO2 hydrogenation catalysis to produce high value-added chemicals. The catalyst adopts a typical sol-gel strategy to construct a series of iron-cobalt bimetallic active catalysts. The synergistic regulation layout of the Fe-Co bimetallic active site catalyst constructs a Fe5C2-FeCo high active interface, and exhibits a high carbon dioxide conversion rate (56.9%), a low carbon monoxide selectivity (3.6%), and an excellent light olefin selectivity (40.5%). BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 XRD characterization results of the catalysts of Examples 3, 4, and 5;

[0055] Figure 2 SEM and EDS characterization results of catalysts in Examples 3 and 5 0.02 Fe2Co1(a)and Na 0.02 Fe1Co2(b);

[0056] Figure 3 Comparative Examples 1 and 2: SEM and EDS characterization results of catalysts 0.02 Co3O4(a)and Na 0.02 Fe2O3(b). DETAILED DESCRIPTION

[0057] The present invention provides a Fe-Co bimetallic active site catalyst and a preparation method and application thereof. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they all fall within the scope of protection of the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.

[0058] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.

[0059] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.

[0060] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0061] In this application, "at least one" means one or more, "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items.

[0062] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the present invention remains operable. In addition, two or more steps or actions may be performed simultaneously.

[0063] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the invention and does not limit the scope of the invention unless otherwise claimed. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the invention.

[0064] In addition, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values ​​in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values ​​and percentages used in this disclosure are modified by "about". Here, "about" generally means that the actual value is within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.

[0065] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0066] Some cases are recorded in the embodiments and comparative examples of the present invention, wherein the embodiments show certain implementation modes of the present invention. However, this does not mean that the effects of the present invention can only be achieved in these cases.

[0067] In order to further illustrate the present invention, a Fe-Co bimetallic active site catalyst provided by the present invention, a preparation method thereof and an application thereof are described in detail below in conjunction with embodiments.

[0068] Comparative Example 1

[0069] Take 0.030 mol of Fe(NO3)3·9H2O and dissolve it in 200 mL of deionized water, and stir it thoroughly at 60°C for 2 hours. Then add 0.04 mol of citric acid monohydrate to the above solution, continue heating for 2 hours, and then increase the temperature to 90°C until a gel-like complex is formed. The obtained gel is transferred to a muffle furnace, calcined at 400°C for 2 hours, and then cooled to room temperature and ground to obtain Fe2O3.

[0070] The obtained solid was ground and washed with ethanol for 3 times, and then placed in an oven at 100°C for 10 h; 1 / 3 of the above solid was taken into a crucible, 0.2 mmol of NaNO3 was weighed and dissolved in an appropriate amount of deionized water, and then the NaNO3 solution was dripped into the crucible and ultrasonicated until the solution was evaporated to dryness, and Na 0.02 Fe2O3.

[0071] Figure 3 Comparative Examples 1 and 2: SEM and EDS characterization results of catalysts 0.02 Co3O4(a)and Na 0.02 Fe2O3(b).

[0072] The reduction activation process of the catalyst was carried out on a fixed bed, and the reduction conditions were: pure hydrogen as the reducing gas (purity ≥ 99%), the reducing gas flow rate was 60 mL / min, the temperature was raised to 400°C under normal pressure and maintained for 8 hours. Reaction conditions: the ratio of the raw gas was H2 / CO2 / Ar = 68 / 27 / 5 (v / v / v), the raw gas flow rate was 20 mL / min, the reaction pressure and temperature were 3.0 MPa and 320°C, respectively. The catalytic reaction results are shown in Table 1. Figure 3 Comparative Examples 1 and 2: SEM and EDS characterization results of catalysts 0.02 Co3O4(a)and Na0.02 Fe2O3(b).

[0073] Comparative Example 2

[0074] Take 0.030 mol of Co(NO3)2·6H2O and dissolve it in 200 mL of deionized water, and stir it thoroughly at 60°C for 2 hours. Then add 0.04 mol of citric acid monohydrate to the above solution, continue heating for 2 hours, and then increase the temperature to 90°C until a gel composite is formed. The obtained gel is transferred to a muffle furnace, calcined at 400°C for 2 hours, and then cooled to room temperature and ground to obtain Co3O4.

[0075] The obtained solid was ground and washed with ethanol for 3 times, and then placed in an oven at 100°C for 10 h; 1 / 3 of the above solid was taken into a crucible, 0.2 mmol of NaNO3 was weighed and dissolved in an appropriate amount of deionized water, and then the NaNO3 solution was dripped into the crucible and ultrasonicated until the solution was evaporated to dryness, and Na 0.02 Co3O4.

[0076] Figure 3 Comparative Examples 1 and 2: SEM and EDS characterization results of catalysts 0.02 Co3O4(a)and Na 0.02 Fe2O3(b).

[0077] The reduction activation process of the catalyst was carried out on a fixed bed, and the reduction conditions were: pure hydrogen as the reducing gas (purity ≥ 99%), the reducing gas flow rate was 60 mL / min, the temperature was raised to 400°C under normal pressure and maintained for 8 hours. Reaction conditions: the ratio of the raw gas was H2 / CO2 / Ar = 68 / 27 / 5 (v / v / v), the raw gas flow rate was 20 mL / min, the reaction pressure and temperature were 3.0 MPa and 320°C, respectively. The catalytic reaction results are shown in Table 1.

[0078] Example 3

[0079] Usually, 0.020mol Fe(NO3)3·9H2O and 0.010mol Co(NO3)2·6H2O are dissolved in 200mL deionized water, stirred at 60℃ for 2h, then 0.04mol monohydrated citric acid is added to the above solution, heated continuously for 2h, and then the temperature is raised to 90℃ until a gel-like complex is formed. The obtained gel is transferred to a muffle furnace, calcined at 400℃ for 2h, and then cooled to room temperature to obtain spinel CoFe2O4, named Fe2Co1.

[0080] The obtained solid was ground and washed with ethanol for 3 times, and then placed in an oven at 100°C for 10 h. 1 / 2 of the above solid was taken into a crucible, 0.2 mmol of NaNO3 was weighed and dissolved in an appropriate amount of deionized water, and then the NaNO3 solution was dripped into the crucible and ultrasonicated until the solution was evaporated to dryness. Na 0.02 Fe2Co1.

[0081] The reduction activation process of the catalyst was carried out on a fixed bed, and the reduction conditions were: pure hydrogen as the reducing gas (purity ≥ 99%), the reducing gas flow rate was 60 mL / min, the temperature was raised to 400°C under normal pressure and maintained for 8 hours. Reaction conditions: the ratio of the raw gas was H2 / CO2 / Ar = 68 / 27 / 5 (v / v / v), the raw gas flow rate was 20 mL / min, the reaction pressure and temperature were 3.0 MPa and 320°C, respectively. The catalytic reaction results are shown in Table 1. Figure 1 XRD characterization results of catalysts in Examples 3, 4, and 5; Figure 1 It can be seen that, compared with the JCPDS: NO.3-864 standard spectrum, spinel structure diffraction peaks are present in Example 3.

[0082] Figure 2 SEM and EDS characterization results of catalysts in Examples 3 and 5 0.02 Fe2Co1(a)and Na 0.02 Fe1Co2(b); Figures 2-3 The SEM results of the embodiments and comparative examples are shown. Figure 2 It can be seen that the catalyst of the embodiment is in a relatively small block shape, and Fe and Co can be uniformly dispersed in the catalyst.

[0083] Example 4

[0084] Usually, 0.015 mol Fe(NO3)3·9H2O and 0.015 mol Co(NO3)2·6H2O are dissolved in 200 mL of deionized water, stirred at 60°C for 2 h, and then 0.04 mol of citric acid monohydrate is added to the above solution, heated continuously for 2 h, and then the temperature is raised to 90°C until a gel-like complex is formed. The obtained gel is transferred to a muffle furnace, calcined at 400°C for 2 h, and then cooled to room temperature, named Fe1Co1.

[0085] The obtained solid was ground and washed with ethanol for 3 times, and then placed in an oven at 100°C for 10 h. 2 / 3 of the above solid was taken into a crucible, 0.2 mmol of NaNO3 was weighed and dissolved in an appropriate amount of deionized water, and then the NaNO3 solution was dripped into the crucible and ultrasonicated until the solution was evaporated to dryness. Na 0.02 Fe1Co1.

[0086] The reduction activation process of the catalyst was carried out on a fixed bed, and the reduction conditions were: pure hydrogen as the reducing gas (purity ≥ 99%), the reducing gas flow rate was 60 mL / min, the temperature was raised to 400°C under normal pressure and maintained for 8 hours. Reaction conditions: the ratio of the raw gas was H2 / CO2 / Ar = 68 / 27 / 5 (v / v / v), the raw gas flow rate was 20 mL / min, the reaction pressure and temperature were 3.0 MPa and 320°C, respectively. The catalytic reaction results are shown in Table 1. Figure 1 XRD characterization results of catalysts in Examples 3, 4, and 5; Figure 1 It can be seen that compared with the JCPDS: NO.3-864 standard spectrum, there is a spinel structure diffraction peak in Example 4.

[0087] Example 5

[0088] Usually, 0.010 mol Fe(NO3)3·9H2O and 0.020 mol Co(NO3)2·6H2O are dissolved in 200 mL of deionized water, stirred at 60°C for 2 h, and then 0.04 mol of citric acid monohydrate is added to the above solution, heated continuously for 2 h, and then the temperature is raised to 90°C until a gel-like complex is formed. The obtained gel is transferred to a muffle furnace, calcined at 400°C for 2 h, and then cooled to room temperature, named Fe1Co2.

[0089] The obtained solid was ground and washed with ethanol for 3 times, and then placed in an oven at 100°C for 10 h. The above solid was placed in a crucible, 0.2 mmol of NaNO3 was weighed and dissolved in an appropriate amount of deionized water, and then the NaNO3 solution was dripped into the crucible and ultrasonicated until the solution was evaporated to dryness. Na 0.02 Fe1Co2.

[0090] The reduction activation process of the catalyst was carried out on a fixed bed, and the reduction conditions were: pure hydrogen as the reducing gas (purity ≥ 99%), the reducing gas flow rate was 60 mL / min, the temperature was raised to 400°C under normal pressure and maintained for 8 hours. Reaction conditions: the ratio of the raw gas was H2 / CO2 / Ar = 68 / 27 / 5 (v / v / v), the raw gas flow rate was 20 mL / min, the reaction pressure and temperature were 3.0 MPa and 320°C, respectively. The catalytic reaction results are shown in Table 1.

[0091] Figure 1 The XRD characterization results of the catalysts of Examples 3, 4, and 5 are shown in FIG. Figure 1 It can be seen that compared with the JCPDS: NO.3-864 standard spectrum, there is a spinel structure diffraction peak in Example 5.

[0092] Example 6

[0093] Usually, 0.015 mol Fe(NO3)3·9H2O and 0.015 mol Co(NO3)2·6H2O are dissolved in 200 mL of deionized water, stirred at 60°C for 2 h, and then 0.04 mol of citric acid monohydrate is added to the above solution, heated continuously for 2 h, and then the temperature is raised to 90°C until a gel-like complex is formed. The obtained gel is transferred to a muffle furnace, calcined at 400°C for 2 h, and then cooled to room temperature, named Fe1Co1.

[0094] The obtained solid was ground and washed with ethanol for 3 times, and then placed in an oven at 100°C for 10 h. 2 / 3 of the above solid was taken into a crucible, 0.1 mmol of NaNO3 was weighed and dissolved in an appropriate amount of deionized water, and then the NaNO3 solution was dripped into the crucible and ultrasonicated until the solution was evaporated to dryness, and Na 0.01 Fe1Co1.

[0095] The reduction activation process of the catalyst was carried out on a fixed bed, and the reduction conditions were: pure hydrogen as the reducing gas (purity ≥ 99%), the reducing gas flow rate was 60 mL / min, the temperature was raised to 400°C under normal pressure and maintained for 8 hours. Reaction conditions: the ratio of the raw gas was H2 / CO2 / Ar = 68 / 27 / 5 (v / v / v), the raw gas flow rate was 20 mL / min, the reaction pressure and temperature were 3.0 MPa and 320°C, respectively. The catalytic reaction results are shown in Table 1.

[0096] Example 7

[0097] Usually, 0.015 mol Fe(NO3)3·9H2O and 0.015 mol Co(NO3)2·6H2O are dissolved in 200 mL of deionized water, stirred at 60°C for 2 h, and then 0.04 mol of citric acid monohydrate is added to the above solution, heated continuously for 2 h, and then the temperature is raised to 90°C until a gel-like complex is formed. The obtained gel is transferred to a muffle furnace, calcined at 400°C for 2 h, and then cooled to room temperature, named Fe1Co1.

[0098] The obtained solid was ground and washed with ethanol for 3 times, and then placed in an oven at 100°C for 10 h. 2 / 3 of the above solid was taken into a crucible, 0.3 mmol of NaNO3 was weighed and dissolved in an appropriate amount of deionized water, and then the NaNO3 solution was dripped into the crucible and ultrasonicated until the solution was evaporated to dryness, and Na 0.03 Fe1Co1.

[0099] The reduction activation process of the catalyst was carried out on a fixed bed, and the reduction conditions were: pure hydrogen as the reducing gas (purity ≥ 99%), the reducing gas flow rate was 60 mL / min, the temperature was raised to 400°C under normal pressure and maintained for 8 hours. Reaction conditions: the ratio of the raw gas was H2 / CO2 / Ar = 68 / 27 / 5 (v / v / v), the raw gas flow rate was 20 mL / min, the reaction pressure and temperature were 3.0 MPa and 320°C, respectively. The catalytic reaction results are shown in Table 1.

[0100] Example 8

[0101] Usually, 0.015 mol Fe(NO3)3·9H2O and 0.015 mol Co(NO3)2·6H2O are dissolved in 200 mL of deionized water, stirred at 60°C for 2 h, and then 0.04 mol of citric acid monohydrate is added to the above solution, heated continuously for 2 h, and then the temperature is raised to 90°C until a gel-like complex is formed. The obtained gel is transferred to a muffle furnace, calcined at 400°C for 2 h, and then cooled to room temperature, named Fe1Co1.

[0102] The obtained solid was ground and washed with ethanol for 3 times, and then placed in an oven at 100°C for 10 h. 2 / 3 of the above solid was taken into a crucible, 0.4 mmol of NaNO3 was weighed and dissolved in an appropriate amount of deionized water, and then the NaNO3 solution was dripped into the crucible and ultrasonicated until the solution was evaporated to dryness, and Na 0.04 Fe1Co1.

[0103] The reduction activation process of the catalyst was carried out on a fixed bed, and the reduction conditions were: pure hydrogen as the reducing gas (purity ≥ 99%), the reducing gas flow rate was 60 mL / min, the temperature was raised to 400°C under normal pressure and maintained for 8 hours. Reaction conditions: the ratio of the raw gas was H2 / CO2 / Ar = 68 / 27 / 5 (v / v / v), the raw gas flow rate was 20 mL / min, the reaction pressure and temperature were 3.0 MPa and 320°C, respectively. The catalytic reaction results are shown in Table 1.

[0104] Example 9

[0105] Usually, 0.015 mol Fe(NO3)3·9H2O and 0.015 mol Co(NO3)2·6H2O are dissolved in 200 mL of deionized water, stirred at 60°C for 2 h, and then 0.04 mol of citric acid monohydrate is added to the above solution, heated continuously for 2 h, and then the temperature is raised to 90°C until a gel-like complex is formed. The obtained gel is transferred to a muffle furnace, calcined at 400°C for 2 h, and then cooled to room temperature, named Fe1Co1.

[0106] The obtained solid was ground and washed with ethanol for 3 times, and then placed in an oven at 100°C for 10 h. 2 / 3 of the above solid was taken into a crucible, 0.2 mmol of NaNO3 was weighed and dissolved in an appropriate amount of deionized water, and then the NaNO3 solution was dripped into the crucible and ultrasonicated until the solution was evaporated to dryness. Na 0.02 Fe1Co1.

[0107] The reduction activation process of the catalyst was carried out on a fixed bed, and the reduction conditions were: pure hydrogen as the reducing gas (purity ≥ 99%), the reducing gas flow rate was 60 mL / min, the temperature was raised to 400°C under normal pressure and maintained for 8 hours. Reaction conditions: the ratio of the raw gas was H2 / CO2 / Ar = 68 / 27 / 5 (v / v / v), the raw gas flow rate was 20 mL / min, the reaction pressure and temperature were 3.0 MPa and 300°C, respectively. The catalytic reaction results are shown in Table 1.

[0108] Example 10

[0109] Usually, 0.015 mol Fe(NO3)3·9H2O and 0.015 mol Co(NO3)2·6H2O are dissolved in 200 mL of deionized water, stirred at 60°C for 2 h, and then 0.04 mol of citric acid monohydrate is added to the above solution, heated continuously for 2 h, and then the temperature is raised to 90°C until a gel-like complex is formed. The obtained gel is transferred to a muffle furnace, calcined at 400°C for 2 h, and then cooled to room temperature, named Fe1Co1.

[0110] The obtained solid was ground and washed with ethanol for 3 times, and then placed in an oven at 100°C for 10 h. 2 / 3 of the above solid was taken into a crucible, 0.2 mmol of NaNO3 was weighed and dissolved in an appropriate amount of deionized water, and then the NaNO3 solution was dripped into the crucible and ultrasonicated until the solution was evaporated to dryness. Na 0.02 Fe1Co1.

[0111] The reduction activation process of the catalyst was carried out on a fixed bed, and the reduction conditions were: pure hydrogen as the reducing gas (purity ≥ 99%), the reducing gas flow rate was 60 mL / min, the temperature was raised to 400°C under normal pressure and maintained for 8 hours. Reaction conditions: the ratio of the raw gas was H2 / CO2 / Ar = 68 / 27 / 5 (v / v / v), the raw gas flow rate was 20 mL / min, the reaction pressure and temperature were 3.0 MPa and 340°C, respectively. The catalytic reaction results are shown in Table 1.

[0112] Embodiment 11

[0113] Usually, 0.015 mol Fe(NO3)3·9H2O and 0.015 mol Co(NO3)2·6H2O are dissolved in 200 mL of deionized water, stirred at 60°C for 2 h, and then 0.04 mol of citric acid monohydrate is added to the above solution, heated continuously for 2 h, and then the temperature is raised to 90°C until a gel-like complex is formed. The obtained gel is transferred to a muffle furnace, calcined at 400°C for 2 h, and then cooled to room temperature, named Fe1Co1.

[0114] The obtained solid was ground and washed with ethanol for 3 times, and then placed in an oven at 100°C for 10 h. 2 / 3 of the above solid was taken into a crucible, 0.2 mmol of NaNO3 was weighed and dissolved in an appropriate amount of deionized water, and then the NaNO3 solution was dripped into the crucible and ultrasonicated until the solution was evaporated to dryness. Na 0.02 Fe1Co1.

[0115] The reduction activation process of the catalyst was carried out on a fixed bed, and the reduction conditions were: pure hydrogen as the reducing gas (purity ≥ 99%), the reducing gas flow rate was 60 mL / min, the temperature was raised to 400°C under normal pressure and maintained for 8 hours. Reaction conditions: the ratio of the raw gas was H2 / CO2 / Ar = 68 / 27 / 5 (v / v / v), the raw gas flow rate was 20 mL / min, the reaction pressure and temperature were 3.0 MPa and 360°C, respectively. The catalytic reaction results are shown in Table 1.

[0116] Example 12

[0117] Usually, 0.015 mol Fe(NO3)3·9H2O and 0.015 mol Co(NO3)2·6H2O are dissolved in 200 mL of deionized water, stirred at 60°C for 2 h, and then 0.04 mol of citric acid monohydrate is added to the above solution, heated continuously for 2 h, and then the temperature is raised to 90°C until a gel-like complex is formed. The obtained gel is transferred to a muffle furnace, calcined at 400°C for 2 h, and then cooled to room temperature, named Fe1Co1.

[0118] The obtained solid was ground and washed with ethanol for 3 times, and then placed in an oven at 100°C for 10 h. 2 / 3 of the above solid was taken into a crucible, 0.2 mmol of NaNO3 was weighed and dissolved in an appropriate amount of deionized water, and then the NaNO3 solution was dripped into the crucible and ultrasonicated until the solution was evaporated to dryness. Na 0.02 Fe1Co1.

[0119] The reduction activation process of the catalyst was carried out on a fixed bed, and the reduction conditions were: pure hydrogen as the reducing gas (purity ≥ 99%), the reducing gas flow rate was 60 mL / min, the temperature was raised to 400°C under normal pressure and maintained for 8 hours. Reaction conditions: the ratio of the raw gas was H2 / CO2 / Ar = 68 / 27 / 5 (v / v / v), the raw gas flow rate was 20 mL / min, the reaction pressure and temperature were 1.0 MPa and 340°C, respectively. The catalytic reaction results are shown in Table 1.

[0120] Embodiment 13

[0121] Usually, 0.015 mol Fe(NO3)3·9H2O and 0.015 mol Co(NO3)2·6H2O are dissolved in 200 mL of deionized water, stirred at 60°C for 2 h, and then 0.04 mol of citric acid monohydrate is added to the above solution, heated continuously for 2 h, and then the temperature is raised to 90°C until a gel-like complex is formed. The obtained gel is transferred to a muffle furnace, calcined at 400°C for 2 h, and then cooled to room temperature, named Fe1Co1.

[0122] The obtained solid was ground and washed with ethanol for 3 times, and then placed in an oven at 100°C for 10 h. 2 / 3 of the above solid was taken into a crucible, 0.2 mmol of NaNO3 was weighed and dissolved in an appropriate amount of deionized water, and then the NaNO3 solution was dripped into the crucible and ultrasonicated until the solution was evaporated to dryness. Na 0.02 Fe1Co1.

[0123] The reduction activation process of the catalyst was carried out on a fixed bed, and the reduction conditions were: pure hydrogen as the reducing gas (purity ≥ 99%), the reducing gas flow rate was 60 mL / min, the temperature was raised to 400°C under normal pressure and maintained for 8 hours. Reaction conditions: the ratio of the raw gas was H2 / CO2 / Ar = 68 / 27 / 5 (v / v / v), the raw gas flow rate was 20 mL / min, the reaction pressure and temperature were 2.0 MPa and 340°C, respectively. The catalytic reaction results are shown in Table 1.

[0124] Embodiment 14

[0125] Usually, 0.015 mol Fe(NO3)3·9H2O and 0.015 mol Co(NO3)2·6H2O are dissolved in 200 mL of deionized water, stirred at 60°C for 2 h, and then 0.04 mol of citric acid monohydrate is added to the above solution, heated continuously for 2 h, and then the temperature is raised to 90°C until a gel-like complex is formed. The obtained gel is transferred to a muffle furnace, calcined at 400°C for 2 h, and then cooled to room temperature, named Fe1Co1.

[0126] The obtained solid was ground and washed with ethanol for 3 times, and then placed in an oven at 100°C for 10 h. 2 / 3 of the above solid was taken into a crucible, 0.2 mmol of NaNO3 was weighed and dissolved in an appropriate amount of deionized water, and then the NaNO3 solution was dripped into the crucible and ultrasonicated until the solution was evaporated to dryness. Na 0.02 Fe1Co1.

[0127] The reduction activation process of the catalyst was carried out on a fixed bed, and the reduction conditions were: pure hydrogen as the reducing gas (purity ≥ 99%), the reducing gas flow rate was 60 mL / min, the temperature was raised to 400°C under normal pressure and maintained for 8 hours. Reaction conditions: the ratio of the raw gas was H2 / CO2 / Ar = 68 / 27 / 5 (v / v / v), the raw gas flow rate was 20 mL / min, the reaction pressure and temperature were 4.0 MPa and 340°C, respectively. The catalytic reaction results are shown in Table 1.

[0128] Embodiment 15

[0129] Usually, 0.015 mol Fe(NO3)3·9H2O and 0.015 mol Co(NO3)2·6H2O are dissolved in 200 mL of deionized water, stirred at 60°C for 2 h, and then 0.04 mol of citric acid monohydrate is added to the above solution, heated continuously for 2 h, and then the temperature is raised to 90°C until a gel-like complex is formed. The obtained gel is transferred to a muffle furnace, calcined at 400°C for 2 h, and then cooled to room temperature, named Fe1Co1.

[0130] The obtained solid was ground and washed with ethanol for 3 times, and then placed in an oven at 100°C for 10 h. 2 / 3 of the above solid was taken into a crucible, 0.2 mmol of NaNO3 was weighed and dissolved in an appropriate amount of deionized water, and then the NaNO3 solution was dripped into the crucible and ultrasonicated until the solution was evaporated to dryness. Na 0.02 Fe1Co1.

[0131] The reduction activation process of the catalyst was carried out on a fixed bed, and the reduction conditions were: pure hydrogen as the reducing gas (purity ≥ 99%), the reducing gas flow rate was 60 mL / min, the temperature was raised to 400°C under normal pressure and maintained for 8 hours. Reaction conditions: the ratio of the raw gas was H2 / CO2 / Ar = 68 / 27 / 5 (v / v / v), the raw gas flow rate was 20 mL / min, the reaction pressure and temperature were 5.0 MPa and 340°C, respectively. The catalytic reaction results are shown in Table 1.

[0132] Table 1 Effect of all catalysts on CO2 hydrogenation performance

[0133]

[0134]

[0135] Reaction conditions: H2 / CO2 / Ar=68% / 27% / 5%, TOS=8h, GHSV=4800mL g -1 h -1 .

[0136] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a Fe-Co bimetallic active site catalyst, characterized in that: The steps include: A) mixing iron salt, cobalt salt and citric acid, heating and stirring to dissolve, and heating to obtain a gel composite; B) continuing to heat the gel composite and then calcining it to obtain a Fe-Co solid catalyst; C) dropping the sodium salt solution into the Fe-Co solid catalyst, ultrasonicating, drying and grinding to obtain the Fe-Co bimetallic active site catalyst.

2. The preparation method according to claim 1, characterized in that: The iron salt is nitrate, acetate or chloride of iron; the cobalt salt is nitrate, acetate or chloride of cobalt.

3. The preparation method according to claim 1, characterized in that: The molar ratio of iron to cobalt in the Fe-Co bimetallic active site catalyst is 0.5-2; the molar ratio of the electron auxiliary agent Na is 0.01-0.04 with reference to Fe.

4. The preparation method according to claim 1, characterized in that: Step A) the temperature of heating, stirring and dissolving is 20-60°C for 1-3h; the temperature of heating is 70-120°C; The citric acid is aqueous citric acid or anhydrous citric acid; the molar ratio of the added amount of the citric acid to the metal content is 4:

3.

5. The preparation method according to claim 1, characterized in that: Step B) The calcination is carried out in a muffle furnace, and the calcination parameters include: heating to 300-700° C. at a heating rate of 0.5-10° C. / min, calcining for 2-8 hours, and then cooling to room temperature.

6. The preparation method according to claim 1, characterized in that: Step C) the sodium salt is sodium carbonate, sodium bicarbonate or sodium nitrate; The drying step is drying in an oven at 70 to 120° C. for 2 to 12 hours; and the grinding step is granulating the powder into 10 to 60 mesh sizes after grinding.

7. A Fe-Co bimetallic active site catalyst, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the Fe-Co bimetallic active site catalyst prepared by the preparation method according to any one of claims 1 to 6 in the preparation of light olefins.

9. A method for synthesizing light olefins by hydrogenation of CO2, characterized in that: include: The Fe-Co bimetallic active site catalyst prepared by the preparation method according to any one of claims 1 to 6 is subjected to reduction activation and then subjected to hydrogenation reaction using CO2 as the reaction gas in the presence of a mixture of H2 and Ar.

10. The method according to claim 9, characterized in that The molar ratio of H2:CO2 in the mixed gas is 0.1-5, and the mixed gas flow rate ranges from 5-80 mL / min; the hydrogenation reaction temperature is 180-550° C., and the hydrogenation reaction pressure ranges from 0.1-6 MPa; The reduction activation parameters include: using pure hydrogen (purity ≥ 99%) at normal pressure, heating to 200-800° C. at a heating rate of 0.5-15° C. / min and maintaining for 2-12 hours; The low-carbon olefin is an olefin having 2 to 4 carbon atoms.

Citation Information

Patent Citations

  • Application of iron-based catalyst in catalyzing carbon dioxide hydrogenation to synthesize low-carbon olefin

    CN112174764A